miR-146a and miR-155 Expression Levels in Acute Graft-Versus-Host Disease Incidence - Atarod, Sadaf; Ahmed, Mohammed Mahid; Lendrem, Clare; Pearce, Kim Frances; Cope, Wei; Norden, Jean; Wang, Xiao-Nong; Collin, Matthew; Dickinson, Anne Mary (Frontiers in Immunology, 2016)
Allogeneic haematopoietic stem cell transplantation (allo-HSCT) is a curative treatment for numerous haematological malignancies. However, acute graft-versus-host disease (aGVHD) is still the major complication causing mortality. MicroRNAs (miRNAs) play a significant role in inflammation and have potential as prognostic and diagnostic biomarkers. This study investigated the role of two immune-specific miRNAs (miR-146a and miR-155) as biomarkers for aGVHD incidence in the peripheral blood of allo-HSCT patients prior to disease onset. The study showed that miR-146a and its (statistical) interaction with miR-155 at day+28 was predictive of aGVHD incidence. Interestingly, the expression levels of miR-146a and miR-155 negatively correlated with the transcription factor, SPI1 (PU.1gene) mRNA expression.